Crosstalk between secondary messengers, hormones and MAPK modules during abiotic stress signalling in plants - Smékalová, Veronika; Doskočilová, Anna; Komis, George; Samaj, Jozef (Biotechnology advances, 2014)
The crosstalk between second messengers, hormones and mitogen-activated protein kinases (MAPKs) in plant signalling systems facilitates adaptation and survival in the face of diverse environmental stresses. This review focuses on the transduction of second messenger and hormone signals by MAPK modules in plant abiotic stress responses. We discuss how this crosstalk regulates gene expression (e.g. by controlling transcription factor activity) and other cellular and physiological responses to enable adaptation and/or resistance to abiotic stresses.
Keywords: Second messenger; Stress, Physiological; Stress; regulátory růstu rostlin; signální transdukce; Signalling; Plant; Plant Growth Regulators; fyziologický stres; Mitogen-activated protein kinase; Cross-talk; Plant Physiological Phenomena; mitogenem aktivované proteinkinasy; fyziologie rostlin; Mitogen-Activated Protein Kinases; Signal Transduction; Hormone